Advantages and Limitations of Gene Therapy and Gene Editing for Friedreich’s Ataxia - Sivakumar, Anusha; Cherqui, Stephanie (Frontiers in Genome Editing, 2022)
Friedreich’s ataxia (FRDA) is an inherited, multisystemic disorder predominantly caused by GAA hyper expansion in intron 1 of frataxin (FXN) gene. This expansion mutation transcriptionally represses FXN, a mitochondrial protein that is required for iron metabolism and mitochondrial homeostasis, leading to neurodegenerative and cardiac dysfunctions. Current therapeutic options for FRDA are focused on improving mitochondrial function and increasing frataxin expression through pharmacological interventions but are not effective in delaying or preventing the neurodegeneration in clinical trials. Recent research on in vivo and ex vivo gene therapy methods in FRDA animal and cell models showcase its promise as a one-time therapy for FRDA. In this review, we provide an overview on the current and emerging prospects of gene therapy for FRDA, with specific focus on advantages of CRISPR/Cas9-mediated gene editing of FXN as a viable option to restore endogenous frataxin expression. We also assess the potential of ex vivo gene editing in hematopoietic stem and progenitor cells as a potential autologous transplantation therapeutic option and discuss its advantages in tackling FRDA-specific safety aspects for clinical translation.